Oralidad, prácticas y objetos sagrados del chamanismo cofán en la comunidad de Pisurie - 2014 - Disse, Malin Ea Delphino Franco (2015)
This investigation about the orality, the practices and the sacred objects of the shamanism of the A’í nationality in the year 2014, is based on a teorical, temporal and spatial approach, from an anthropological perspective. It gives an understanding of the orality of the A’í, showing the most important characteristics of the language, the discourse and the shamanic words that are found in the shamanic wisdom of this socio-culture. The thesis explores the mythological dimension of the A’í, tradition in the community of Pisurie Canqque. It analyses the difference between shamanism and sorcery or black magic and discusses the importance of shamanic songs in this nationality and its use of visionary plants, such as the sacred yagé substance. The thesis discusses how the influence of the catholic and occidental cosmo-vision transformed the A’í shamanism. The practical aspects of A’i shamanism are expressed in rituality. The thesis discusses the nationality’s understanding of illnesses, the practice of the “shamanic seeing” and the practice with sacred objects that the shaman Don Avelino Quenamá uses to lead the rituals. Important in the A’í nationality are the rituals of initiation, healing and the ritual to prepare the visionary substance of the yagé. The thesis also analyses the belief system surrounding A’í rituality and discusses the relationship between the A’í shamanism and the spiritual and political dimensions of the nationality. The thesis concludes that, in order to conserve their tradition, the A’í nationality is living a “war of the senses”, symbolically, which is expressed in the spiritual and political dimensions of their nationality.